Distributive Justice Perspective of Sharia Economic Law in Indonesia - Mugni Muhit; Rani Mariana; Mohamad Anton Athoillah (CV. Media Digital Publikasi Indonesia, 2023)
Injustice is a traditional and current issue that all economic systems encounter. This economic injustice and disparity of income and wealth is the origin of the poverty problem. The idea of distributive justice emerged in Islamic economics in response to the inability of current economic theories to address the issues of poverty, income, and wealth disparity. As a result, the study of distribution has long been an intriguing topic in Islamic economics. This study defines distribution from an Islamic economic standpoint, examines problems related to injustice in the Indonesian distribution system, criticizes capitalist economic distribution, and concludes with a study of Islamic economic distribution in discovering distributive justice and distribution mechanisms in Islam as an answer for justice and social welfare